2009
DOI: 10.1182/blood-2008-08-175208
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of CD20 expression in B-cell lymphoma cells after treatment with rituximab-containing combination chemotherapies: its prevalence and clinical significance

Abstract: Although rituximab is a key molecular targeting drug for CD20-positive B-cell lymphomas, resistance to rituximab has recently been recognized as a considerable problem. Here, we report that a CD20-negative phenotypic change after chemotherapies with rituximab occurs in a certain number of CD20-positive B-cell lymphoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
189
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(200 citation statements)
references
References 44 publications
6
189
0
5
Order By: Relevance
“…Loss of CD20 and other B-cell marker expression has been associated with more aggressive clinical behavior and poor prognosis. 12,13 However, this loss of B-cell markers has not previously been described in association with the uniform strong CD30 expression that was seen in our case.…”
Section: Commentmentioning
confidence: 39%
“…Loss of CD20 and other B-cell marker expression has been associated with more aggressive clinical behavior and poor prognosis. 12,13 However, this loss of B-cell markers has not previously been described in association with the uniform strong CD30 expression that was seen in our case.…”
Section: Commentmentioning
confidence: 39%
“…3,4 There are two emerging issues to be resolved for better usage of this drug: weak effects on some tumors [6][7][8] and drug resistance. 5,[9][10][11] In this study, we clearly demonstrated that HDAC inhibitors, VPA and romidepsin, potentiated the cytotoxic effect of rituximab against Burkitt lymphoma, which has innate resistance to rituximab, 7 by enhancing the expression of surface CD20 antigen both in vitro and in vivo. We also analyzed the mechanisms of CD20 upregulation and found that HDAC inhibitors acetylated core histones of CD20 promoter to enhance the binding of Sp1, leading to transactivation of the CD20 gene in BJA-B and Namalwa cells.…”
Section: Discussionmentioning
confidence: 83%
“…8 Furthermore, several cases of CD20-negative relapse were identified after treatment with rituximab-based regimens in diffuse large B-cell lymphoma. 9,10 Recently, Hiraga et al 11 reported that relapse or disease progression was observed in B30% of patients with B-cell lymphomas treated with rituximab-containing chemotherapies, and CD20 expression was lost in 5 of 19 relapsed patients who underwent repeated biopsy. It is of note that DNAdemethylating agents restored CD20 expression in lymphoma cells isolated from these patients, suggesting that epigenetic mechanisms underlie the downregulation of CD20 after rituximab treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of such resistance has not been fully elucidated, however, a number of reports on the potential mechanisms of resistance after rituximab mono-therapy or R-CHOP combination therapy have been suggested. These include loss or down-regulation of CD20 membrane expression, histological transformation and up-regulation of anti-apoptotic molecules including bcl-2 (29)(30)(31)(32). We are currently examining whether BM-ca, alone or in combination with chemotherapy, exerts an activity, not seen with rituximab, on rituximabresistant B-NHL cell lines.…”
Section: Discussionmentioning
confidence: 99%